2006
DOI: 10.1002/bdra.20275
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a functional genetic polymorphism of the human retinoic acid–metabolizing enzyme CYP26A1, an enzyme that may be involved in spina bifida

Abstract: Despite the fact that our findings could not show any evidence that the CYP26A1 genetic polymorphism has implications in the pathogenesis of spina bifida, this work represents the first description of a functional genetic polymorphism affecting the coding sequence of the human CYP26A1 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Our experimental results emphasize the loss‐of‐function characteristics of these rare mutations encoding for the RA degradation enzyme CYP26B1 . Our findings together with genetic association studies by others (Deak et al., ; Rat et al., ; Tran et al., ) highlight this functional pathway in the genetic contribution of rare mutations to human NTDs.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our experimental results emphasize the loss‐of‐function characteristics of these rare mutations encoding for the RA degradation enzyme CYP26B1 . Our findings together with genetic association studies by others (Deak et al., ; Rat et al., ; Tran et al., ) highlight this functional pathway in the genetic contribution of rare mutations to human NTDs.…”
Section: Discussionsupporting
confidence: 82%
“…A polymorphism discovery screen was carried out for ALDH1A2 (MIM# 603687), CYP26A1 (MIM# 602239), CYP26B1 (MIM# 605207), CRABP1 (MIM# 180230), and CRABP2 (MIM# 180231) genes in 230 individuals with lumbosacral myelomeningocele (including spina bifida aperta or spina bifida cystica), and a significant association between three polymorphisms in ALDH1A2 and this spinal NTD was identified (Deak et al., ). In another study, a deletion (g.3116delT) in the CYP26A1 gene, which creates a premature stop codon, was found in a sample of 40 spina bifida patients of Caucasian origin from southern Italy (Rat et al., ). Moreover, investigation of the three RA receptors encoded by RARA (MIM# 180240), RARB (MIM# 180220), and RARG (MIM# 180190) in 329 affected family trios and 281 affected family duos of patients with meningomyelocele from Texas, identified SNPs in each of these genes and these were associated with a protective effect against meningomyelocele (Tran et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Mice lacking either Cyp26a1 or Aldh1a2 display an open neural tube (Abu-Abed et al, 2001;Ribes et al, 2006), and human mutations in both ALDH1A2 and CYP26A1 have been linked to spina bifida (Deak et al, 2005;Rat et al, 2006). These results suggest that too much or too little RA is deleterious for neural tube closure.…”
Section: Discussionmentioning
confidence: 81%
“…Some congenital defects that are consistent with retinoid embryopathy and have been either mechanistically or anecdotally associated with functional defects in CYP26 enzymes include spina bifida and cleft palate, DiGeorge syndrome, and Klippel‐Feil anomaly (De Marco et al,2006; Rat et al,2006; Roberts et al,2006; Laue et al,2008). Mutational screening of CYP26A1 polymorphisms in patients with spina bifida and caudal regression syndrome revealed that SNPs exist that affect the rate of RA metabolism, but none were homozygous and were not able to be statistically linked to the observed phenotypes (De Marco et al,2006; Rat et al,2006). These studies suggested that CYP26A1 mutations may not play a predominant causative role in spina bifida or caudal regression syndrome, but the small cohorts used in each study may not have allowed for the detection of the potentially rare incidence of involvement of hypomorphs/mutations of CYP26A1.…”
Section: Associations Of Cyp26 Mutations With Human Congenital Malformentioning
confidence: 99%